Bismuth Iodoform Paraffin Paste [bipp] Wick versus Topical Levofloxacin Drops in Rapid Drying of Wet Ear in Tubotympainic Chronic Suppurative Otitis Media - Said Mustafa Said Al Jaff (Advanced Medical Journal)
Background and objectives:Topical ear drops have been the mainstay in the medical management of actively dis- charging chronic suppurative otitis media with central perforation. Bismuth Iodoform Paraffin Paste has been used over the past 30 years for various clinical purposes on skin and mucosa without any serious local or systemic ad- verse effects. The aim of this study was to evaluate if Bismuth Iodoform Paraffin Paste can be used topically in the treatment of chronic superlative otitis media–tub tympanic disease and to compare it with Levofloxacin ear drops.